Studi Kualitatif Dukungan Keluarga Pasien Penderita Gagal Ginjal Pada Usia Dewasa Yang Melakukan Perawatan Cuci Darah Di Rumah Sakit Bahteramas Provinsi Sulawesi Tenggara Tahun 2023 - Finna Eka Arum Sari; Hartati Bahar; Zainab Hikmawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Kidney function loss is known as renal failure. When a patient's kidney function falls below 10%, they are diagnosed with end-stage renal disease (ESRD). A dialyzer is used to circulate the patient's blood during hemodialysis, a kidney replacement treatment. Metabolic waste products are then removed from the bloodstream, particularly those resulting from the metabolism of proteins. The purpose of this study is to comprehend the level of family support provided to adult patients with renal failure who are receiving hemodialysis at Bahteramas Hospital in the province of Southeast Sulawesi in 2023. The case study methodology of the qualitative research makes use of documenting, recording, interviewing, and observation techniques. The results show the many ways families help their dialysis patients with renal failure. Hemodialysis therapy includes a number of support options. First, informational assistance Second, instrumental assistance; third, evaluative support; and, last, emotional support